2016
DOI: 10.3171/2015.4.peds14411
|View full text |Cite
|
Sign up to set email alerts
|

Routine perioperative ketorolac administration is not associated with hemorrhage in pediatric neurosurgery patients

Abstract: OBJECT NSAIDs are effective perioperative analgesics. Many surgeons are reluctant to use NSAIDs perioperatively because of a theoretical increase in the risk for bleeding events. The authors assessed the effect of routine perioperative ketorolac use on intracranial hemorrhage in children undergoing a wide range of neurosurgical procedures. METHODS A retrospective single-institution analysis of 1451 neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
(29 reference statements)
0
25
0
Order By: Relevance
“…The maximum dose of 30 mg of ketorolac was chosen in accordance with the maximum intravenous dose. It is notable that a single dose of ketorolac is considered safe even if a patient may undergo surgery . In our series, ketorolac and tramadol were not superior to paracetamol in managing pain, but children, who took tramadol experienced significantly more adverse events.…”
Section: Discussionmentioning
confidence: 59%
“…The maximum dose of 30 mg of ketorolac was chosen in accordance with the maximum intravenous dose. It is notable that a single dose of ketorolac is considered safe even if a patient may undergo surgery . In our series, ketorolac and tramadol were not superior to paracetamol in managing pain, but children, who took tramadol experienced significantly more adverse events.…”
Section: Discussionmentioning
confidence: 59%
“…The greater bleeding volume in the ketorolac group may be the reason for the higher heart rate in these patients. Richardson et al assessed 1,451 pediatric patients undergoing cranial surgery, and concluded that short-term ketorolac therapy was not associated with significantly increased bleeding on postoperative imaging or clinical evaluation ( 22 ). Jahangiri compared the efficacy of paracetamol and remifentanil for postoperative pain management in patients undergoing coronary artery bypass graft surgery, and showed better analgesic effects with paracetamol ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The patients underwent a standard anesthesia with ketamine 1 mg/kg, midazolam 0.1 mg/kg, and fentanyl [1][2][3][4][5] µg/kg for induction and atracurium 0.6 mg/kg to facilitate endotracheal intubation. Anesthesia was maintained with isoflurane 1.2 -2.5 minimum alveolar concentration (MAC) and additional fentanyl 5 µg/kg to maintain blood pressure and heart rates at 20% from baseline.…”
Section: Methodsmentioning
confidence: 99%
“…However, their safety is questioned in children undergoing heart surgery. Ketorolac has been used safely to manage postoperative pain in different pediatric surgeries (3)(4)(5)(6)(7)(8) including congenital heart surgery (9-11) with no adverse effects.…”
Section: Introductionmentioning
confidence: 99%